PENGARUH KEBIJAKAN FISKAL DAN MONETER TERHADAP PERTUMBUHAN EKONOMI PROVINSI JAMBI - Mahdi, Mahdi; Aimon, Hasdi; Syofyan, Efrizal (Jurnal Kajian Ekonomi, 2014)
This study aims to analyze and determine the effect of: (1) government spending on economic growth Jambi province, (2) taxes on economic growth Jambi, (3) the money supply to economic growth Jambi and (4) interest rates on economic growth Jambi province.. This research uses the methods of analysis tools Ordinary Least Squared (OLS). The dependent variable in the study of economic growth. While the independent variable in this study is government spending, taxes, the money supply and interest rates. The research concludes that (1) government spending significant and positive impact on economic growth of Jambi Province. (2) taxes affect economic growth Jambi significantly and negatively. (3) the money supply is also a positive effect on economic growth signifikandan Jambi Province. (4) interest rates affect economic growth Jambi significantly and negatively. Based on these results the policies that can be advised Local Government (LG) is the need for local government or policy makers efforts by increasing government spending (Expansionary Fiscal Policy). The Government is expected to set the proper allocation of tax so as not to weaken the purchasing power of consumers. The Government is expected to set the proper allocation of tax so as not to weaken the purchasing power of consumers. Local government and Bank Indonesia in order to maintain liquidity or the availability of money in the economy Jambi. Government along the banks especially Bank Indonesia in order to maintain a healthy rate so it does not impact on the decline in the interest of investors to invest. Keyword : Fiscal Policy, Moneter Policy, Government Expenditure, Tax, Money Supply, Interest Rate